Companion to sexuality studies - Naples, Nancy A. (Wiley Blackwell, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres